Pengaruh Komunikasi Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru SMK-Kartika 1-2 Padang - Shandy Marta Wijaya; Defhany (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
Kartika 1-2 Padang Vocational School is one of the private schools engaged in education which is under the auspices of the Kartika Jaya Foundation. In an effort to achieve this vision, good performance is needed from teachers and staff involved in managing teaching and learning activities at SMK Kartika 1-2 Padang. Weaknesses in teacher performance included the finding that a number of class teachers did not make a Learning Implementation Plan (RPP) correctly and had not been corrected and signed by the school principal but had been used as a guide in learning. The principal has many important tasks and one of them is communicating with the teacher teaching in the classroom. In the communication process, several factors are involved, namely the communicator, message, media, and communicant. The purpose of this study is the dominant indicator of the principal's leadership communication on the performance of teachers and employees of SMK-Kartika 1-2 Padang and to determine the influence of the principal's leadership on the performance of teachers of SMK-Kartika 1-2 Padang. This study uses a type of quantitative research. The sampling technique is the Total Sampling technique. The sample of this research is all teachers who teach at SMK-Kartika 1-2 Padang. Simple linear regression analysis was used to test the hypothesis with the SPSS 24 program. The results of this study indicate that the most influential indicator of the Principal Leadership Communication variable, namely vertical communication, is in the good category. Principal Leadership Communication influences Teacher Performance. Principals should improve leadership communication effectively with good communication directions, so that teachers can actualize the various competencies they have. Thus, the teacher's performance is getting better/increased. For teachers of SMK-Kartika 1-2 Padang, so that they can also communicate effectively both between teachers, and with superiors, or even with students so that communication is better and improving teacher performance in the future